Customizable chitosan microfiber-based water sponge gel as well as preparation method and application thereof

By preparing customizable chitosan microfiber-based hydrosponge gels with large pore structures, the problems of small mesh size and lack of customizability of traditional hydrogels have been solved, enabling the repair of large-volume soft tissue defects and exhibiting excellent biocompatibility and biodegradability.

CN119286045AActive Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411432131.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Traditional hydrogels have small mesh sizes in their three-dimensional polymer networks, which affects nutrient transport and lacks customizability, making them unsuitable for repairing large-volume soft tissue defects. Furthermore, existing scaffold materials have issues with biocompatibility and biodegradability.

Method used

Chitosan acid solution was sheared, pH was adjusted to alkaline, and an epoxy crosslinking agent was added to form a chitosan microfiber hydrogel precursor. Subsequently, centrifugation and multiple freeze-thaw cycles were performed to prepare a customizable chitosan microfiber-based hydrosponge gel with a large pore structure.

Benefits of technology

The prepared customizable chitosan microfiber-based water sponge gel has a rich porous structure, which improves the transport efficiency of nutrients and waste. It also has excellent elasticity, fatigue resistance, biocompatibility and biodegradability, making it suitable for repairing and reconstructing large-volume soft tissue defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286045A_ABST
    Figure CN119286045A_ABST
Patent Text Reader

Abstract

The invention discloses customizable chitosan microfiber-based water sponge gel as well as a preparation method and application thereof, and the preparation method comprises the following steps: shearing an acid solution of chitosan, and adjusting the pH value of a system to be alkaline, so as to obtain a chitosan microfiber solution; and adding an epoxy cross-linking agent, and carrying out freeze thawing treatment on the precipitate obtained by centrifugal treatment for multiple times by using the covalent bond and hydrogen bond cross-linked chitosan microfiber to prepare the water sponge gel. The customizable chitosan microfiber-based water sponge gel prepared by the method disclosed by the invention has abundant macroporous structures, so that the transmission efficiency of nutrient substances and wastes can be effectively improved, and two-dimensional and three-dimensional customizable structures with different shapes can be obtained by extruding chitosan microfiber suspension liquid through an injector; the prepared scaffold has excellent elasticity, fatigue resistance, low hysteretic property, biocompatibility and degradability, meets the requirements of large-scale preparation of various scaffolds with complex structures, and is expected to be used as a customizable implantable scaffold for repairing and reconstructing large-volume soft tissue defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of soft tissue repair engineering materials, and relates to a customizable chitosan microfiber-based water sponge gel, a preparation method and application thereof. Background Art

[0002] Accidents or surgical procedures (such as debridement and tumor resection) can cause skin, fat, muscle, flaps or combined soft tissue injuries, resulting in large soft tissue defects. The treatment methods for repairing and reconstructing large soft tissues are usually autologous flap transplantation, autologous fat transplantation and prosthesis implantation. However, these treatments cause serious complications. Autologous flap transplantation requires the transplantation of soft tissue from other parts of the body to the defect site, resulting in donor site defects; large amounts of transplanted autologous fat are easily absorbed by the human body and usually require repeated injections; prosthetic implants are prone to foreign body reactions, leading to fibrosis, hematoma and capsular contracture. At present, there is a lack of scaffold materials that can perfectly treat large soft tissue defects. Therefore, the strategy of designing scaffolds for repairing and reconstructing large soft tissue defects remains a bottleneck problem that needs to be solved urgently in the field of tissue engineering, highlighting the importance of developing customizable viscoelastic biomaterials.

[0003] Hydrogels have become the most promising implantable scaffold materials due to their soft tissue-like properties. However, the small mesh size (about tens of nanometers) and bound water in the three-dimensional polymer network structure of traditional hydrogels limit the long-distance transport of gases and nutrients (>150 μm), resulting in the inability to meet the repair needs of large-volume soft tissue defects. Therefore, it is urgent to design and prepare new large-pore, hydrated, flexible implantable scaffolds to meet the needs of repairing and reconstructing large-volume soft tissue defects. New hydrosponge gel (hydrogel / sponge) materials with highly porous structures and excellent water-holding properties have both the viscoelasticity of hydrogels and the reversible compression properties of sponges, and are expected to play a role in repairing and reconstructing large-volume soft tissue defects. However, most hydrosponge gels are derived from petrochemical-derived synthetic materials and are potentially toxic. Natural polymer materials have the advantages of wide sources, low cost, biocompatibility, and biodegradability. However, balancing the structural customizability and mechanical properties of hydrosponge gels based on natural biopolymer materials remains challenging. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a customizable chitosan microfiber-based water sponge gel and a preparation method and application thereof, so as to solve the technical problems of the small mesh size in the three-dimensional polymer network of the current traditional hydrogel, which affects the transmission of nutrients and is not customizable.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a customizable chitosan microfiber-based water sponge gel comprises the following steps: S1: Shearing the acid solution of chitosan to adjust the pH to alkaline to prepare a chitosan microfiber solution, adding an epoxy crosslinking agent to react with the chitosan microfibers to obtain a hydrogel precursor; S2: centrifuging the hydrogel precursor, and subjecting the obtained precipitate to multiple freeze-thaw treatments to prepare the customizable chitosan microfiber-based hydrosponge gel.

[0006] Preferably, in step S1, the chitosan acid solution is prepared by dispersing chitosan in a hydrochloric acid solution and stirring; the volume concentration of the hydrochloric acid solution is 0.4% to 0.5%.

[0007] Preferably, in step S1, during the shearing treatment, the shear rate is 8000-11000 rad / min, the shearing time is 4-7 min, and the shearing temperature is 25-37 °C.

[0008] Preferably, the epoxy crosslinking agent is any one of epichlorohydrin, polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol glycidyl ether and sorbitol glycidyl ether.

[0009] Preferably, the chitosan has a deacetylation value of 75% to 85% and a molecular weight of 9000 to 50000 Da.

[0010] Preferably, the ratio of chitosan to epoxy crosslinking agent in the chitosan acid solution is (5-1) g:1 mL.

[0011] Preferably, in step S2, the freeze-thaw treatment includes a freezing process and a thawing process, wherein the freezing temperature is -20 to -24 °C, and the freezing time is 12 to 18 h; the thawing temperature is 25 to 37 °C, and the thawing time is 2 to 4 h.

[0012] Preferably, in step S2, after the hydrogel precursor is centrifuged, the precipitate obtained by centrifugation is squeezed out through a syringe to form two-dimensional or three-dimensional structures of different shapes, and freeze-thaw treatment is performed multiple times to obtain chitosan microfiber-based hydrosponge gels of two-dimensional or three-dimensional structures of different shapes.

[0013] A customizable chitosan microfiber-based water sponge gel is prepared by the above method; the average diameter of the pore structure in the customizable chitosan microfiber-based water sponge gel is 20-40 μm.

[0014] The above-mentioned customizable chitosan microfiber-based water sponge gel is used in repairing and reconstructing large soft tissue defects.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a customizable chitosan microfiber-based water sponge gel. First, a chitosan acid solution is sheared to make the chitosan long chain shear orientation consistent, shorten its molecular chain length, and obtain chitosan microfibers. Due to the shortening of the chitosan microfiber length, the specific surface area of ​​the material increases, and the number of active functional groups increases, which creates favorable conditions for the subsequent cross-linking reaction. At the same time, the process also helps to improve the dispersibility of chitosan in water. Subsequently, under alkaline conditions, an epoxy cross-linking agent is added to undergo an epoxy ring-opening reaction, and a covalent bond is formed with the amino and hydroxyl groups on the chitosan microfibers, forming a larger volume of pore structure between the chitosan microfibers. Subsequently, a hydrogel precursor is subjected to a freezing treatment. During the freezing treatment, the water inside the precursor forms ice crystals, and the free chitosan microfibers in the system are reorganized and regenerated for a second time, and then thawed, so that the free chitosan after reorganization and regeneration in the water sponge gel undergoes precipitation and phase change processes, which is more conducive to the water sponge gel system to perform network cross-linking. After multiple freeze-thaw treatments, a water sponge gel with a larger network structure is formed. The customizable chitosan microfiber-based water sponge gel prepared by the method of the present invention has a rich pore structure, which effectively increases the transmission efficiency of nutrients and wastes. In addition, the chitosan microfiber suspension can be extruded through a syringe to obtain two-dimensional and three-dimensional customizable structures of different shapes. It has excellent elasticity, fatigue resistance, low hysteresis, biocompatibility and degradability, and is expected to be used to repair and reconstruct large-volume soft tissue defects.

[0016] In addition, the present invention also discloses a customizable chitosan microfiber-based water sponge gel prepared by the above method, wherein the average diameter of the mesopore structure of the customizable chitosan microfiber-based water sponge gel is 20-40 μm, which can meet the requirements of effective transmission of nutrients. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 Schematic diagram of bonding between chitosan and epoxy crosslinking agent of the present invention; Figure 2 The XRD patterns of the customizable chitosan microfiber-based water sponge gels prepared in Examples 1 to 4 of the present invention; Figure 3 FTIR spectra of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention; Figure 4 The XPS spectrum of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention; Figure 5 This is a SEM image of the customizable chitosan microfiber-based water sponge gel prepared in the present invention; Figure 6 The mechanical properties test results of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention are shown in Figure 1. (a) is the comparison result of the storage modulus (G') and the loss modulus (G''), and (b) is the comparison result of the elasticity of the customizable chitosan microfiber water sponge gel; Figure 7 These are the anti-fatigue test results of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention, wherein (a) is the test curve, and (b) is the Young's modulus self-recovery rate of the customizable chitosan microfiber-based water sponge gel after resting time.

[0019] Figure 8 The water holding performance test results of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention, wherein (a) is a representative weight loss curve of the compression strain (0% to 90%) of the customizable chitosan microfiber-based water sponge gel; the viscoelastic region and the pore elastic region are divided at the yield point; (b) is the yield point of the customizable chitosan microfiber-based water sponge gel under compression pressure.

[0020] Fig. 9 In order to utilize the customizability of the customizable chitosan microfiber-based water sponge gel prepared in Example 1 of the present invention, (a) is a viscosity test, (b) is a test schematic diagram, and (c) is a product with different molding properties.

[0021] Fig.10 The biocompatibility test results of the customizable chitosan microfiber-based water sponge gel prepared in Example 1 of the present invention at different time periods in vitro; (a) is the live / dead cell staining of the control group and the customizable chitosan microfiber water sponge gel extract and cells after 24 h, 48 h, and 72 h of co-culture (scale: 100 µm), and (b) is the hemolysis rate data and hemolysis photos of the customizable chitosan microfiber-based water sponge gel.

[0022] Fig.11 The tissue compatibility of the hydrosponge gel, where (a) is the pathological section result of the main organs (heart, liver, spleen, lung, and kidney) observed 28 days after subcutaneous implantation in SD rats, and (b) is the pathological section of the surrounding tissues of the hydrosponge gel implanted in SD rats; Fig.12In vivo blood toxicity test results of customizable chitosan microfiber-based water sponge gel, where (a) is the liver function index and (b) is the kidney function index. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions).

[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0028] The present invention provides a method for preparing a customizable chitosan microfiber-based water sponge gel, comprising the following steps: S1: The chitosan acid solution is sheared and the pH is adjusted to be alkaline, and the epoxy crosslinking agent undergoes an epoxy ring-opening reaction to crosslink the chitosan microfibers through covalent bonds and hydrogen bonds, and after stirring the reaction, a hydrogel precursor is obtained; The acid solution of chitosan is prepared by dispersing chitosan in a hydrochloric acid solution and stirring; the volume concentration of the hydrochloric acid solution is 0.4% to 0.5%.

[0029] During the shearing treatment, the shearing speed is 8000-11000 rad / min, the shearing time is 4-7 min, and the shearing temperature is 25-37 °C.

[0030] The epoxy crosslinking agent is any one of epichlorohydrin, polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol glycidyl ether and sorbitol glycidyl ether.

[0031] The deacetylation value of the chitosan is 75%-85%, and the molecular weight is 9000-50000 Da.

[0032] Preferably, the pH value of the adjustment system is 7-8.5.

[0033] More preferably, the ratio of chitosan to epoxy crosslinking agent in the chitosan acid solution is (1-5) g:1 mL.

[0034] S2: centrifuging the hydrogel precursor, and subjecting the obtained precipitate to multiple freeze-thaw treatments to prepare the customizable chitosan microfiber hydrosponge gel.

[0035] During the centrifugal treatment, the rotation speed is 5000~6000 rad / min and the time is 10~15 min.

[0036] The freeze-thaw treatment includes the freezing process and the thawing process, in which the freezing temperature is -20~-24 °C and the freezing time is 12~18 h; the thawing temperature is 25~37 °C and the thawing time is 2~4 h.

[0037] Among them, in the preferred embodiment, the number of freeze-thaw cycles is 1 to 4 times.

[0038] like Figure 1 As shown, the present invention discloses a method for preparing a customizable chitosan microfiber-based water sponge gel. First, chitosan is selected as the main component, and epichlorohydrin, polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol glycidyl ether or sorbitol glycidyl ether is selected as an epoxy crosslinking agent, and the chitosan long chain shear orientation is made consistent through high-speed homogenization shearing treatment. The epoxy crosslinking agent undergoes an epoxy ring-opening reaction under alkaline conditions to form a covalent bond with the amino or hydroxyl group on the chitosan microfiber chain. Further freeze-thaw treatment causes the chitosan microfiber chain to regenerate and reorganize the secondary reorganization, and gives the water sponge gel a porous structure and excellent self-healing properties. The customizable chitosan microfiber-based water sponge gel prepared by the method of the present invention has a rich porous structure, excellent elasticity, fatigue resistance, low hysteresis, biocompatibility and degradability, and is expected to be used as an implantable scaffold for repairing and reconstructing large soft tissue defects.

[0039] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0040] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0041] Example 1 A method for preparing a customizable chitosan microfiber-based water sponge gel, comprising the following specific steps: 1.08 g chitosan was weighed and added to 90 mL of 0.46% dilute hydrochloric acid. After stirring until completely dissolved, it was stirred in a high-speed homogenizer at 9000 r for 5 min, and NaOH solution (1 mol / L) was slowly dripped to adjust the pH value to 7.5-8. At the same time, 0.36 mL of epichlorohydrin (ECH) was added as an epoxy crosslinking agent, and it was allowed to stand at room temperature for 5 h. Subsequently, it was centrifuged at 9000 r for 10 min in a high-speed centrifuge, the supernatant was removed, and the resulting precipitate was placed in a cylindrical mold and frozen at -24 °C for 12 h, and thawed at room temperature to prepare a customizable chitosan microfiber-based water sponge gel.

[0042] Example 2 The difference between this embodiment and embodiment 1 is that the epoxy crosslinking agent added is polyethylene glycol diglycidyl ether, wherein the molecular weight of polyethylene glycol diglycidyl ether is 200 Da (PEGDGE-200).

[0043] Example 3 The difference between this embodiment and embodiment 1 is that the epoxy crosslinking agent added is polyethylene glycol diglycidyl ether, wherein the molecular weight of polyethylene glycol diglycidyl ether is 500 Da (PEGDGE-500).

[0044] Example 4 The difference between this embodiment and embodiment 1 is that the epoxy cross-linking agent added is glycerol triglycidyl ether (GTE).

[0045] Example 5 The difference between this embodiment and embodiment 1 is that the epoxy cross-linking agent added is polypropylene glycol glycidyl ether (PPGDGE).

[0046] Example 6 The difference between this embodiment and embodiment 1 is that the epoxy cross-linking agent added is sorbitol glycidyl ether (SPE).

[0047] Example 7 A method for preparing a customizable chitosan microfiber-based water sponge gel comprises the following steps: S1: Chitosan with a deacetylation value of 75% and a molecular weight of 9000 Da is dissolved in a hydrochloric acid solution with a volume concentration of 0.4%, and then sheared, and then the pH value is adjusted to 7, and an epoxy crosslinking agent is added, and the reaction is stirred to obtain a hydrogel precursor. In the shearing process, the shear speed is 8000 rad / min, the shearing time is 7 min, and the shearing temperature is 25 ° C; the epoxy crosslinking agent is epichlorohydrin.

[0048] S2: The hydrogel precursor is centrifuged at a rotation speed of 5000 rad / min for 15 min, and the obtained precipitate is subjected to a cyclic freeze-thaw treatment, wherein the freeze-thaw treatment includes a freezing process and a thawing process, wherein the freezing temperature is -20 °C and the freezing time is 18 h; the thawing temperature is 25 °C and the thawing time is 4 h, to prepare the customizable chitosan microfiber-based hydrosponge gel.

[0049] Example 8 A method for preparing a customizable chitosan microfiber-based water sponge gel comprises the following steps: S1: Chitosan with a deacetylation value of 85% and a molecular weight of 50,000 Da is dissolved in a hydrochloric acid solution with a volume concentration of 0.5%, subjected to shear treatment, and then the pH value is adjusted to 8.5. An epoxy crosslinking agent is added, and after stirring the reaction, a hydrogel precursor is obtained. During the shear treatment, the shear speed is 11,000 rad / min, the shear time is 4 min, and the shear temperature is 37 °C; the epoxy crosslinking agent is polyethylene glycol diglycidyl ether, and the molecular weight of the polyethylene glycol diglycidyl ether is 400.

[0050] S2: The hydrogel precursor is centrifuged at a rotation speed of 6000 rad / min for 10 min, and the obtained precipitate is subjected to multiple cycles of freeze-thaw treatment, wherein the freeze-thaw treatment includes a freezing process and a thawing process, wherein the freezing temperature is -24 °C, the freezing time is 12 h; the thawing temperature is 37 °C, the thawing time is 2 h, and the number of cycles of the cyclic freeze-thaw treatment is 4 times, to prepare the customizable chitosan microfiber-based hydrosponge gel.

[0051] Example 9 A method for preparing a customizable chitosan microfiber-based water sponge gel comprises the following steps: S1: Chitosan with a deacetylation value of 80% and a molecular weight of 20,000 Da is dissolved in a hydrochloric acid solution with a volume concentration of 0.45%, and then sheared, and then the pH value is adjusted to 8, and an epoxy crosslinking agent is added, and the reaction is stirred to obtain a hydrogel precursor. In the shearing process, the shear speed is 10,000 rad / min, the shearing time is 5 min, and the shearing temperature is 30°C; the epoxy crosslinking agent is glycerol triglycidyl ether.

[0052] S2: The hydrogel precursor is centrifuged at a speed of 5500 rad / min for 12 min, and the obtained precipitate is subjected to multiple cycles of freeze-thaw treatment, wherein the freeze-thaw treatment includes a freezing process and a thawing process, wherein the freezing temperature is -22 °C, the freezing time is 15 h; the thawing temperature is 30 °C, the thawing time is 3 h, and the number of cycles of the cyclic freeze-thaw treatment is 2 times, to prepare the customizable chitosan microfiber-based water sponge gel. In order to illustrate the performance of the customizable chitosan microfiber-based water sponge gel prepared in the present invention, the following tests are performed, specifically: Figure 2 The XRD patterns of the customizable chitosan microfiber-based water sponge gels prepared in Examples 1 to 4 of the present invention are compared with the chitosan microfibers (Pure CMFs) obtained after high-speed shearing of chitosan. During the test, the crystal structure of the product was analyzed using X-ray diffraction (XRD) from Bruker, Germany, at 40 kV and 100 mA Cu Kα radiation (wavelength λ = 0.154 nm). Figure 2 It can be seen that pure chitosan shows a characteristic peak of chitosan at 2θ of 20°. This is because there are intermolecular hydrogen bonds between the hydroxyl (-OH) and amino (-NH2) groups in the chitosan structure, resulting in crystals with different chemical structure regions. Although the epoxy cross-linking agents in Examples 1 to 4 are different and the cross-linking degrees of the prepared products are different, all samples have similar diffraction peaks, indicating that the cross-linking agent will not affect the crystallinity of the chitosan microfibers.

[0053] Figure 3 The FTIR spectra of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention (Vertex70, Bruker Corporation, Germany) are compared with those of pure chitosan microfibers. As can be seen from the figure, the pure chitosan microfiber water sponge gel has a FTIR spectrum at 1600 cm −1 、1100cm −1 and 1000 cm −1The vibration peaks were attributed to the primary COC stretching vibration, secondary CO and primary CO stretching vibration, respectively. The vibration peaks of these groups also appeared in the FTIR spectra of epichlorohydrin, polyethylene glycol diglycidyl ether-200, polyethylene glycol diglycidyl ether-500 and glycerol triglycidyl ether water sponge gels. All the customizable chitosan microfiber-based water sponge gels had a peak at 3468 cm -1 The stretching vibrations of -OH and -NH2 appear on the left and right, indicating that the epoxy crosslinker is effectively crosslinked with the chitosan microfibers, that is, a chemical network structure can be effectively formed by crosslinking different epoxy crosslinkers with chitosan microfibers.

[0054] Additionally, the elimination and chemical compositions of the products were examined using X-ray photoelectron spectroscopy (XPS). Figure 4 The XPS spectra of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention, wherein (a) is the spectrum of O 1s, and (b) is the spectrum of N 1s. The results are compared with those of pure chitosan microfiber water sponge gel. It can be seen from the figure that the deconvolution peak analysis of O 1s indicates the presence of COC, -OH and -C=O bonds. Similarly, the deconvolution peak analysis of N 1s at 399.09 eV indicates the presence of neutral amino groups, while the deconvolution peak analysis of COC of O 1s at 400.85 eV corresponds to the protonated amino group. The high ratio of the peak is related to the COC deconvolution peak analysis of O 1s, and the -NH3 deconvolution peak analysis of N 1s reveals that the crosslinking efficiency of glycerol triglycidyl ether with chitosan microfibers is the highest, proving the reaction efficiency of the epoxy crosslinker with chitosan amino groups in the customizable chitosan microfiber-based water sponge gel.

[0055] Furthermore, Figure 5 This is a diagram of the internal pore structure of the customizable chitosan microfiber-based water sponge gel observed by scanning electron microscopy (SEM). The figure shows that the customizable chitosan microfiber-based water sponge gel has a rich porous structure with a pore size of about 20~40 μm, which is conducive to the transport of oxygen and nutrients.

[0056] Furthermore, the mechanical properties of the customizable chitosan microfiber-based water sponge gel prepared by the present invention were tested using an electronic universal testing machine (CMT Shenzhen Sansi, Shenzhen, China) at room temperature (25 °C), a compression rate of 20 mm / min, and a maximum compression strain of 85%. During the test, the customizable chitosan microfiber-based water sponge gel was made into a cylindrical shape (diameter 15 mm, height 18 mm). The test results are as follows Figure 6 shown. Figure 6The mechanical properties of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention, wherein (a) is the comparison result of the storage modulus (G') and the loss modulus (G''), and (b) is the comparison result of the elasticity of the customizable chitosan microfiber-based water sponge gel. The rheological properties of the customizable chitosan microfiber-based water sponge gel (cylindrical shape with a diameter of 10 mm and a height of 2 mm) were tested at 25 °C using a rheometer (DHR-1, TA Instruments, American). The test results are shown in FIG. Figure 7 As shown, in the entire frequency range (0.1 rad / s-100 rad / s), G' is always higher than G'', indicating that the water sponge gel is stable and behaves as an elastic solid. According to G'=kTv (k is the Boltzmann constant, T is the temperature, and v is the cross-linking density of the ideal cross-linking network), the high G' of the chitosan microfiber-based water sponge gel can be tailored, indicating that the chitosan microfibers have a high inter-fiber cross-linking density. By comparing the G' of the water sponge gel cross-linked by epichlorohydrin, polyethylene glycol diglycidyl ether-200 and polyethylene glycol diglycidyl ether-500 epoxy cross-linkers, it can be found that G' increases with the increase of the aliphatic hydrocarbon chain length. This may be because the epoxy cross-linker with a shorter aliphatic hydrocarbon chain length cannot form effective cross-links between chitosan microfibers with larger gaps.

[0057] Furthermore, the fatigue resistance of the customizable chitosan microfiber-based water sponge gel prepared in the present invention was tested using an electronic universal testing machine (CMT Shenzhen Sansi, Shenzhen, China) at room temperature (25 °C), a compression rate of 20 mm / min, and a maximum compression strain of 85%. Figure 7 As shown in the figure, in the loading test, the residual strain refers to the irreversible strain generated after the material enters the plastic stage. The smaller the residual strain, the better the elastic properties. The residual strain of epichlorohydrin water sponge gel (24.8%) is close to that of pure chitosan microfiber water sponge gel (26.4%), because there is only one epoxy group and the short chain of epichlorohydrin does not form effective crosslinking between chitosan microfibers. The residual strain of glycerol triglycidyl ether (5.3%), polyethylene glycol diglycidyl ether-200 (16.9%) and polyethylene glycol diglycidyl ether-500 (14.4%) water sponge gels are all lower than those of epichlorohydrin and pure chitosan microfiber water sponge gel. The lower the residual strain, the better the crosslinking efficiency. Therefore, glycerol triglycidyl ether, polyethylene glycol diglycidyl ether-200 and polyethylene glycol diglycidyl ether-500 have better crosslinking efficiency. The chemical cross-linking effect of the tailorable chitosan microfiber-based hydrosponge gels increased with the increase of epoxy functional groups and aliphatic hydrocarbon chain length.

[0058] Furthermore, the water holding capacity of the customizable chitosan microfiber-based water sponge gel was tested by weighing the weight of water lost under different stress compressions. The test structure is shown in Figure 8 , Figure 8 The test results of the water holding capacity of the customizable chitosan microfiber-based water sponge gel prepared in Examples 1 to 4 of the present invention, wherein (a) is a representative weight loss curve of the compression strain of the customizable chitosan microfiber-based water sponge gel ranging from 0% to 90%. The viscoelastic region and the pore elastic region are divided at the yield point. (b) is the yield point of the customizable chitosan microfiber-based water sponge gel under compression pressure. As can be seen from the figure, the quantitative strain boundary between volume elastic deformation and porous elastic deformation is called the yield point. Below the yield point, the customizable chitosan microfiber-based water sponge gel undergoes viscoelastic deformation, resulting in conformational rearrangement. Above the yield point, the sample undergoes porous elastic deformation, and water is squeezed out of the customizable chitosan microfiber-based water sponge gel. The weight change depending on the strain of the customizable chitosan microfiber-based water sponge gel was measured during the compression test to find the yield point of the chitosan microfiber water sponge gel ( Figure 8 a). As expected, the compressive strain at the yield point increases with increasing interfiber crosslink density. Figure 8 As shown in (b), the glycerol triglycidyl ether water sponge gel exhibited the largest strain (14%) at the yield point, while the pure chitosan microfiber-based water sponge gel had the smallest strain (7.2%). In addition, when the water sponge gel was cross-linked with epichlorohydrin (8.9%), polyethylene glycol diglycidyl ether-200 (9.2%), and polyethylene glycol diglycidyl ether-500 (9.6%), the yield point strain gradually increased. The yield point increased with the increase of chain length. These phenomena indicate that the formation of cross-links between chemical fibers can enhance the volume elasticity of the water sponge gel and prevent the morphological changes of the water sponge gel during volume deformation below the yield point.

[0059] In order to demonstrate the customizability of the hydrogel in the present invention, the customizable chitosan microfiber-based hydrosponge gel solid suspension was extruded into the desired shape through a 25G syringe. Fig. 9 As shown in Figure 2, chitosan microfiber suspensions are solid and have a viscosity as high as 10 at low shear rates. 4 As the shear rate increases from 0.1 rad / s to 100 rad / s, the viscosity decreases linearly and drops sharply to only 10 Pa.s at 100 rad / s. This is due to the orientation of the microcrystalline fibers under shear stress ( Fig. 9 a). This shear-thinning behavior makes the chitosan microfiber suspension extrusion-molding capable. The solid chitosan microfiber suspension can be smoothly extruded from a syringe under pressure and form independent patterns without changing its structure and structure ( Fig. 9b). Based on the outstanding extrusion molding ability of chitosan microfiber suspension, we can prepare various two-dimensional and three-dimensional network structures after chemical cross-linking to obtain customizable chitosan microfiber-based hydrosponge gels with different structures. Fig. 9 c shows the rectangular network, flat circular grid, and triangular network of the customizable chitosan microfiber-based water sponge gel, indicating that the present invention can obtain a chitosan microfiber-based water sponge gel with a customized structure.

[0060] In order to demonstrate the in vitro biocompatibility of the customizable chitosan microfiber-based hydrosponge gel of the present invention, the cell viability, proliferation and blood compatibility were evaluated. Specifically, the human umbilical vein endothelial cells (HUVECs) cells after digestion and centrifugation were resuspended in 1 mL of fresh F-12K complete medium and the extraction medium of different composite hydrosponge gels. 100 μL of the cell suspension was drawn and diluted 10 times, and then 10 μL was drawn for hemocytometer counting and the cell suspension density was diluted to 1×10 4 Then, 1×10 3 The cell suspension of human umbilical vein endothelial cells was evenly inoculated into a 96-well plate and sealed with PBS on all sides. The plate was cultured in a carbon dioxide constant temperature incubator (37 °C, 5% CO2), and the medium was changed every 48 hours. After 24, 48 and 72 hours of culture, the culture medium was discarded, and 100 μL of CCK-8 mixed solution (90 μL of culture medium and 10 μL of CCK-8 staining solution) was added to each well, transferred to the incubator for incubation for 2 hours, and then the absorbance at 450 nm was measured on a microplate reader. Each group of experiments was performed in parallel. The third generation human umbilical vein endothelial cells were selected, and the cells were tested for toxicity using the Live / Dead staining kit. First, 5×10 5The cell suspension of human umbilical vein endothelial cells was inoculated into a 24-well plate containing 1 mL of F-12K complete medium and incubated in a carbon dioxide incubator (37 °C, 5% CO2) for 24 h. Subsequently, the complete medium was replaced with 990 μL of hydrogel culture medium extract and supplemented with 10 μL of FBS. The control group was cultured with 1 mL of fresh F-12K complete medium. After culturing at 37 °C and 5% CO2 for 24, 48, and 72 h, the in vitro cytotoxicity was evaluated using a Live / Dead staining kit. 2 mL of anticoagulated rat blood was taken and 2 mL of hydrogel extracts of different masses (concentration gradients were 50, 100, 500, and 1000 g / mL, respectively) were added. At the same time, 2 mL of anticoagulated blood and 2 mL of saline were mixed as negative controls, and 2 mL of anticoagulated blood and 2 mL of deionized water were mixed as positive controls. After each experiment was mixed evenly, it was placed in a 37 °C constant temperature water bath for 1-3 h and then taken out and allowed to stand. 2 mL of supernatant was taken respectively, and the optical density of each supernatant was detected by UV spectrophotometer and the hemolysis rate was calculated. Fig.10 As shown, the customizable chitosan microfiber-based hydrosponge gels were non-cytotoxic to cells and showed no hemolytic reaction in vitro.

[0061] In vivo biocompatibility evaluation was performed by histological section, blood routine, liver function, and renal function. Specifically, the hydrosponge gel with a diameter of 10 mm and a height of 5 mm was subcutaneously implanted into the back of SD rats under anesthesia with 3% sodium pentobarbital. In brief, the skin was incised from the dorsal midline, the subcutaneous tissue was separated by blunt dissection using vascular forceps, and then the hydrosponge gel was implanted. The results are shown in Fig.11 As shown, after 28 days, the pathological sections of the main organs (heart, liver, spleen, lung, kidney) were observed, indicating that there was no in vivo toxicity. Blood was taken from the inguinal artery of the rats for analysis of blood routine, liver and kidney function and other indicators, indicating that there was no blood toxicity ( Fig.12 ). The customizable chitosan microfiber-based water sponge gel prepared by the present invention has good biocompatibility.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a customizable chitosan microfiber-based water sponge gel, characterized in that: The following steps are involved: S1: Shearing the acid solution of chitosan to adjust the pH to alkaline to prepare a chitosan microfiber solution, adding an epoxy crosslinking agent to react with the chitosan microfibers to obtain a hydrogel precursor; S2: centrifuging the hydrogel precursor, and subjecting the obtained precipitate to multiple freeze-thaw treatments to prepare the customizable chitosan microfiber-based hydrosponge gel.

2. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: In step S1, the chitosan acid solution is prepared by dispersing chitosan in a hydrochloric acid solution and stirring; the volume concentration of the hydrochloric acid solution is 0.4% to 0.5%.

3. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: In step S1, during the shearing process, the shear rate is 8000-11000 rad / min, the shearing time is 4-7 min, and the shearing temperature is 25-37 °C.

4. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: The epoxy crosslinking agent is any one of epichlorohydrin, polyethylene glycol diglycidyl ether, glycerol triglycidyl ether, polypropylene glycol glycidyl ether and sorbitol glycidyl ether.

5. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: The deacetylation value of the chitosan is 75%-85%, and the molecular weight is 9000-50000 Da.

6. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: The ratio of chitosan to epoxy crosslinking agent in the chitosan acid solution is (5-1) g:1 mL.

7. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: In step S2, the freeze-thaw treatment includes a freezing process and a thawing process, wherein the freezing temperature is -20~-24 °C, the freezing time is 12~18 h; the thawing temperature is 25~37 °C, and the thawing time is 2~4 h.

8. The method for preparing a customizable chitosan microfiber-based water sponge gel according to claim 1, characterized in that: In step S2, after the hydrogel precursor is centrifuged, the precipitate obtained by centrifugation is squeezed out through a syringe to form two-dimensional or three-dimensional structures of different shapes, and then freeze-thaw treatment is performed multiple times to prepare chitosan microfiber-based hydrosponge gels of different shapes of two-dimensional or three-dimensional structures.

9. A customizable chitosan microfiber-based water sponge gel, characterized in that: Prepared by the method described in any one of claims 1 to 8; the average diameter of the pore structure in the customizable chitosan microfiber-based water sponge gel is 20 to 40 μm.

10. Use of the customizable chitosan microfiber-based water sponge gel as claimed in claim 9 in repairing and reconstructing large soft tissue defects.

Citation Information

Patent Citations

  • Shape memory chitosan hydrogel and preparation method thereof

    CN112940287A

  • Functional chitosan hemostatic dressing and preparation method thereof

    CN118416276A

  • Stabilizing shear-thinning hydrogels

    US20150202299A1

  • Preparation of composite gels, polymer scaffolds, aggregates and films comprising soluble cross-linked chitosan & uses thereof

    US20240277904A1